Performance stylistics: Deleuze and Guattari, poetry and (corpus) linguistics - O’Halloran, Kieran (International Journal of English Studies, 2012)
Taking as stimulus some key ideas of the French philosopher, Gilles Deleuze, and his collaborator the psychoanalyst, Félix Guattari, I demonstrate an alternative interpretative engagement with poetry. In this approach, a poem is seen as an invitation to the reader to be creative via a web-based, interpretative journey which is individual, edifying and refreshing. This approach allows a poem’s obliqueness and suggestiveness to trigger, randomly, knowledge and resources on the world-wide-web that are new for the reader; in turn, these can be used as fresh perspectives on the poem in order to perform it in individual ways, to ‘fill in’ creatively personas and scenarios in the poem. This web-based engagement with a poem involves stylistic analysis. The web-based element of performance stylistics is centrifugal, taking the reader outside of the poem, travelling from website to website. This centrifugal movement is balanced by a centripetal one which takes the reader into the patterns of the poem. Stylistic analysis meets this centripetal need effectively. Traditionally, stylistic analysis has been used to provide linguistic evidence for interpretation of a literary work. However, influenced by ideas in the work of Deleuze and Guattari, I also use stylistic analysis in a non-traditional way - to mobilise interpretation of a poem. In this article, the poem I use to demonstrate performance stylistics is Robert Frost’s, ‘Putting in the Seed’. Performance stylistics can draw on corpus analysis too.